Preliminary notes on Palma’s measure of inequality - Ostasiewicz, Katarzyna; Vernizzi, Achille (Wstępne uwagi na temat miary nierówności Palmy, 2020)
Based on Palma’s observation that for empirical distributions within the range of the 4th and 9th deciles there are – with a good approximation – 50% of all goods, a new measure was introduced that is in a strong relationship to the Gini index, thus – supposedly – including all the information that it provides. In this paper this relationship is investigated more deeply for cases of some theoretical distributions as well as the relationship of a lower bound of a slightly differently defined ‘middle class’ on the Gini index
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2020, Nr 18 (24), s. 183-195